(untitled) (Journal of Education and Development, 2023)
This study uses an Implicit Association Test and a self-report instrument of explicit beliefs to explore implicit and explicit beliefs and attitudes of pre-service teachers about DLLs. Study participants from one United States University in the Southeast were comprised of participants and non-participants of a study abroad language immersion experience. Overall, pre-service teachers in this study (n = 53) held balanced implicit attitudes about DLLs and positive explicit attitudes. Non-study abroad participants held negative explicit views of second language acquisition and lacked understanding of appropriate pedagogical choices for DLLs as compared to their study abroad participant counterparts.